Haruan Channa striatus: a drug discovery in an AGRO-industry setting - Mat Jais, Abdul Manan (Universiti Putra Malaysia Press, 2010)
Malaysia was ranked twelfth in world ranking of Mega biodiversity countries, as declared by UNESCO in 1997. BUT the question is SO WHAT? Since independence in 1957, none of our natural products have been developed to produce pharmaceutical drugs. Further, no single indigenous species has been made into a tradeable COMMODITY.By 2004, we were no longer ranked among the top twelve mega-biodiversity countries, as we were ranked 14th among the 17 countries listed in 2004. This is because most of our forests have been logged, stripping off the nation’s bio-wealth (Malaysia’s Mega-diversity under threat, 2004 http://www.greenpeace.org/international/press/reports/malaysia-s-mega-diversity-unde). Even now, no one knows for sure what we still have, and what has already been eradicated. Logging has destroyed our forests which we have replaced with mono exotic species i.e. either rubber or palm oil. Terrestrial, freshwater and marine ecosystems are under constant threat. Although 70 % of the earth’s surface is covered by water, the freshwater ecosystem comprises only 2%. However, 12% of all animal species, and 40% of all the recognised fish, which totals about 8,400 species, are in the freshwater ecosystem (http://www.fao.org/sd/EPdirect/EPre0044.htm). Unfortuntely with freshwater ecosystems being reduced, at least one fifth of all freshwater fishes are already extinct or seriously endangered. Further, since 1995, 70% of the world’s marine fishes have been either fully exploited or over fished and depleted.One should also remember that fish is accountable for approximately 17% of the animal protein in the normal human diet, and around 29% in Asia. Hence the loss and degradation of biodiversity in the marine ecosystem is very alarming and will have phenomenal implications on the food and livelihood security of humans. Previously, 75% of the fishes consumed were from nature i.e. wild species, while the remaining 25% was from aquaculture production. Today however, approximately 85% of fish supplies are from aquaculture (http://www.fao.org/sd/EPdirect/EPre0044.htm). In Malaysia, the aquaculture industry is now a priority and the government has projected a 200% increase in production to 600,000 tones in 2010, from 200,000 tonnes last year (http://www. fao.org/fishery/countrysector/naso_malaysia/en). Today, there are 290 freshwater fish species identified in Peninsular Malaysia, more than 100 in Sarawak and 200 in Sabah(http://www.nre.gov.my/opencms/opencms/NRE/BM/Services/Biodiversity/biodiversity.html), and the Haruan C striatus is one of them. Most if not all freshwater aquatic species face fewer risks as compared to land animals which are at risk from diseases such as smallpox, Bovine Spongiform Encephalopathy (BSE) or Mad - Cow Disease (MCD), Japanese encephalitis (JE), Bird Flu (H5N1) and Swine Flu (H1N1) (http://en.wikipedia.org/wiki/Aquaculture). This, among others, is the reason why aquaculture is becoming increasingly more important and hence why the Haruan is now an important option in the field of food and drug discovery